Long noncoding MIAT acting as a ceRNA to sponge microRNA‐204‐5p to participate in cerebral microvascular endothelial cell injury after cerebral ischemia through regulating HMGB1. Issue 5 (19th October 2019) - Deng, Wenjing; Fan, Chenghe; Shen, Ruile; Wu, Yanzhi; Du, Ran; Teng, Junfang
Abstract: This study is applied to the investigation of the long noncoding RNA myocardial infarction associated transcript's (MIAT's) role in regulating the expression of high‐mobility group box 1 (HMGB1) in cerebral microvascular endothelial cell (CMEC) injury after cerebral ischemia by serving as a competitive endogenous RNA (ceRNA) to sponge microRNA‐204‐5p (miR‐204‐5p). The cerebral ischemia model of middle cerebral artery occlusion (MCAO) in rats was established by the suture method, in which rats were injected with empty plasmids and MIAT siRNA plasmids. The cerebral ischemia injury model in vitro was established through oxygen glucose deprivation (OGD) in primary cultured CMECs in rats. The cells were transfected with empty plasmids and MIAT siRNA plasmids. The MIAT/miR‐204‐5p/HMGB1 axis' function in damage and angiogenesis of CMECs were explored. The binding site between MIAT and miR‐204‐5p along with that between miR‐204‐5p and HMGB1 was determined. MIAT was overexpressed in MCAO rats' brain tissue and inhibited MIAT attenuated the injury of brain tissue in MCAO rats. Inhibition of MIAT promoted angiogenesis, promoted miR‐204‐5p expression and inhibited HMGB1 expression in brain tissue of MCAO rats. Inhibition of MIAT reduced CMEC damage, induced angiogenesis of CMECs, increased the number of surviving neurons, promoted miR‐204‐5p expression and inhibited HMGB1 expression in CMECs treated with OGD. MIAT promoted HMGB1 expression by competitive binding to miR‐204‐5p to regulate the injury of CMECs after cerebral ischemia. Our study showed that MIAT promoted HMGB1 expression by competitively binding to miR‐204‐5p to regulate the injury of CMECs after cerebral ischemia.